Strategi Pemasaran Bubuk Kopi Gayo Specialty “Nagayo” di Desa Simpang Peut Kecamatan Kuala Kabupaten Nagan Raya (Studi Kasus UD. Nagan Roasting) - Keumala Fadhiela ND; Roslita Roslita (Department of Agribusiness, Halu Oleo University Jointly with Perhimpunan Ekonomi Pertanian Indonesia - Indonesian Society of Agricultural Economics (PERHEPI/ISAE), 2023)
Gayo Arabica coffee business in Aceh is quite prospective because it is supported by the trend and lifestyle of high coffee drinking behavior of the existence of Micro, Small, and Medium Businesses (MSMEs) active in the Gayo coffee processing industry plays an essential role in boosting the regional economy in Aceh. But marketing strategy problems are often faced by Gayo coffee powder producers, one of which is the lack of product promotion, even though marketing strategy is essential to a company's survival. This research aims to investigate the marketing strategies and challenges for Nagayo specialty coffee powder. This research is a case study at UD. Nagan Roasting is an MSME business for specialty coffee powder (Arabica and Robusta coffee) in Nagan Raya Regency. Data was gathered through observational data, in-depth interviews, and focus groups. The analytical methods used are internal and external factors and SWOT analysis. The results of this study indicate that Nagayo specialty coffee powder in quadrant 1 means that the business of UD. Nagan Roasting is in an advantageous position. Other techniques include focusing on customer happiness by delivering durable items and increasing sales marketing through social media to demonstrate Nagayo's quality. UD. Nagan Roasting has strengths and possibilities, and it can capitalize on them—however, UD. Nagan Roasting needs to increase its promotion to show the quality of the only organic coffee powder business in Nagan Raya Regency, supported by the qualified modern processing equipment.